Decision support system for sustainable hydrogen production: case study of Saudi Arabia - Kaheel, Sultan; Fallatah, Gasem; Luk, Patrick Chi-Kwong; Ibrahim, Khalifa Aliyu; Luo, Zhenhua (Elsevier, 2025)
The global energy sector is undergoing a transition towards sustainable sources, with hydrogen emerging as a promising alternative due to its high energy content and clean-burning properties. The integration of hydrogen into the energy landscape represents a significant advancement towards a cleaner, greener future. This paper introduces an innovative decision support system (DSS) that combines multi-criteria decision-making (MCDM) and decision tree methodologies to optimize hydrogen production decisions in emerging economies, using Saudi Arabia as a case study. The proposed DSS, developed using MATLAB Web App Designer tools, evaluates various scenarios related to demand and supply, cost and profit margins, policy implications, and environmental impacts, with the goal of balancing economic viability and ecological responsibility. The study's findings highlight the potential of this DSS to guide policymakers and industry stakeholders in making informed, scalable, and flexible hydrogen production decisions that align with sustainable development goals. The novel DSS framework integrates two key influencing factors technical and logistical by considering components such as data management, modeling, analysis, and decision-making. The analysis component employs statistical and economic methods to model and assess the costs and benefits of eleven strategic scenarios, while the decision-making component uses these results to determine the most effective strategies for implementing hydrogen production to minimize risks and uncertainties.
Keywords: 40 Engineering; 44 Human Society; 7 Affordable and Clean Energy; 12 Responsible Consumption and Production; Energy; Hydrogen economy; Market penetration feasibility; Production capacity; Cost and efficiency; Strategic planning; Hydrogen energy influencing factors